Androgen Regulation in Spermatogenesis to Increase Male Fertility - Hasbi Hasbi; Sri Gustina (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
Male fertility is affected by quantity and quality of sperm which controlled by androgens (testosterone and 5α-dihydrotestosterone) mediated by androgen receptors (AR). Androgen receptors belong to receptor group of steroid hormone and a group of ligand-activated nuclear receptor superfamily. This paper explains androgen hormone and its regulation in spermatogenesis to increase male fertility. Regulation of androgen hormone in spermatogenesis include initiation of spermatogenesis, proliferation and maturation of Sertoli cells, germ cell development, spermatogonia, meiosis, and spermiogenesis. The role of androgen hormone in regulation of spermatogenesis is influenced by AR, luteinizing hormone (LH), and follicle stimulating hormone (FSH) levels. Disruption of spermatogenesis will cause low male fertility. However, low concentrations of AR, LH and FSH could be enhanced by exogenous gonadotrophine releasing hormone (GnRH), LH, FSH, and testosterone to increase male fertility.